Association of Homocysteine Levels with Cardiometabolic Risk Factors Reported at a Tertiary Care Unit of Karachi - Pakistan - Muhammad Sarwar; Iftikhar Ahmed Siddiqui; Anas Alhajwan; Raisat Ali Khan; Asher Fawwad; Abdul Basit (Pakistan Journal of Medical Research, 2022)
Objective: To determine the association between homocysteine serum levels and metabolic risk factors in adults of Karachi – Pakistan.